2021
DOI: 10.1155/2021/3774423
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning-Based CT Imaging in the Quantitative Evaluation of Chronic Kidney Diseases

Abstract: This study focused on the application of deep learning algorithms in the segmentation of CT images, so as to diagnose chronic kidney diseases accurately and quantitatively. First, the residual dual-attention module (RDA module) was used for automatic segmentation of renal cysts in CT images. 79 patients with renal cysts were selected as research subjects, of whom 27 cases were defined as the test group and 52 cases were defined as the training group. The segmentation results of the test group were evaluated fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…34 By the concept that biomedical images contain information that reflects underlying pathophysiology, radiomics can quantitatively analyze the pathological characteristics hidden behind medical images. 13 In recent years, several studies have reported that medical images could be useful for detecting kidney damage and fibrosis, by using ultrasound images, 2628 computed tomography (CT), 3537 and magnetic resonance imaging (MRI). 3840 Zhu et al 28 extracted radiomics features from the shear wave elastography (SWE) ultrasound images and concluded that SWE can predict kidney injury progression with an improved performance by radiomics (AUC = 0.809).…”
Section: Discussionmentioning
confidence: 99%
“…34 By the concept that biomedical images contain information that reflects underlying pathophysiology, radiomics can quantitatively analyze the pathological characteristics hidden behind medical images. 13 In recent years, several studies have reported that medical images could be useful for detecting kidney damage and fibrosis, by using ultrasound images, 2628 computed tomography (CT), 3537 and magnetic resonance imaging (MRI). 3840 Zhu et al 28 extracted radiomics features from the shear wave elastography (SWE) ultrasound images and concluded that SWE can predict kidney injury progression with an improved performance by radiomics (AUC = 0.809).…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [ 28 ], Haghighi et al [ 29 ], and Mehta et al [ 30 ] used fully connected convolutional networks to segment kidney images. Fu et al [ 31 ] used ultrasound images to input an attention module to segment kidney cysts in CT images. Da Cruz et al [ 32 ] presented a fully automated method for segmenting kidneys with and without tumours on CT images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have been various segmentation tasks associated with kidneys, such as kidney segmentation [ 16 ], cyst segmentation [ 17 ], tumor segmentation [ 18 ], and cortex segmentation [ 19 ]. Manual kidney segmentation, such as region-of-interest (ROI) border tracing [ 20 ] or stereology [ 21 ] by experienced and qualified professionals, is considered the gold standard.…”
Section: Related Workmentioning
confidence: 99%